Hypoglycemic and in vitro antioxidant effects of methanolic extract of Marsilea quadrifolia Plant - Zahan, Ronok; Ripa, Farhana Alam; Alam, M. Badrul; Haque, M. Anamul; Mosaddik, M.A.; Nahar, Laizuman (© 2011 Pharmacognosy Journal, 2016)
This article was published in Pharmacognosy Journal [© 2011 Pharmacognosy Journal] and the definite version is available at: https://goo.gl/4T47PD